Reproductive state and rank influence patterns of meat consumption in wild female chimpanzees (Pan troglodytes schweinfurthii). Issue 90 (January 2016) - O'Malley, Robert C.; Stanton, Margaret A.; Gilby, Ian C.; Lonsdorf, Elizabeth V.; Pusey, Anne; Markham, A. Catherine; Murray, Carson M.
Abstract: An increase in faunivory is a consistent component of human evolutionary models. Animal matter is energy- and nutrient-dense and can provide macronutrients, minerals, and vitamins that are limited or absent in plant foods. For female humans and other omnivorous primates, faunivory may be of particular importance during the costly periods of pregnancy and early lactation. Yet, because animal prey is often monopolizable, access to fauna among group-living primates may be mediated by social factors such as rank. Wild chimpanzees ( Pan troglodytes ) across Africa habitually consume insects and/or vertebrates. However, no published studies have examined patterns of female chimpanzee faunivory during pregnancy and early lactation relative to non-reproductive periods, or by females of different rank. In this study, we assessed the influence of reproductive state and dominance rank on the consumption of fauna (meat and insects) by female chimpanzees of Gombe National Park, Tanzania. Using observational data collected over 38 years, we tested (a) whether faunivory varied by reproductive state, and (b) if high-ranking females spent more time consuming fauna than lower-ranking females. In single-factor models, pregnant females consumed more meat than lactating and baseline (meaning not pregnant and not in early lactation) females, and high-ranking females consumed more meat than lower-ranking females. A two-factor analysis of a subset of well-sampled females identified an interaction between rank and reproductive state: lower-ranking females consumed more meat during pregnancy than lower-ranking lactating and baseline females did. High-ranking females did not significantly differ in meat consumption between reproductive states. We found no relationships between rank or reproductive state with insectivory. We conclude that, unlike insectivory, meat consumption by female chimpanzees is mediated by both reproductive state and social rank. We outline possible mechanisms for these patterns, relate our findings to meat-eating patterns in women from well-studied hunter-gatherer societies, and discuss potential avenues for future research.